Pengaruh Pembelajaran Era New Normal Terhadap Kualitas Pembelajaran dan Tingkat Pemahaman IPS - Isnaini Mauludinia; Saiful Amin (Journal Pendidikan Ilmu Pengetahuan Sosial, 2022)
The education system in Indonesia is experiencing new challenges caused by the Covid-19 pandemic that has entered Indonesia since 2020. This causes Indonesia to enter a new normal era. The new normal era learning process which is carried out directly in the classroom is different from face-to-face learning before the pandemic. The purpose of this study was to (1) determine the effect of new normal era learning on the quality of learning of social studies; and (2) determine the effect of learning in the new normal era on the level of understanding of social studies. This research method uses a quantitative approach to the type of correlational research. The participant in this study were students of class VII at SMP (Junior High School) Muhammadiyah 06 Dau, Malang, Indonesia with a total of 75 students. The data collection instrument used a questionnaire. The hypothesis test used is the correlation coefficient test, the coefficient of determination, simple linear regression and partial t test with the classical assumption test in the form of normality test, linearity test, homogeneity test, and heteroscedasticity test. The results showed that (1) learning in the new normal era had a significant effect on the quality of learning with a value of 0.000; and (2) learning in the new normal era had a significant effect on the level of understanding of students with a value of 0.002. Based on the research, it can be concluded that learning in the new normal era has an effect on the quality of learning and the level of students' understanding of social studies at SMP Muhammadiyah 06 Dau. The existence of this research is expected for all parties to make good use of face-to-face learning in the new normal era and develop this research as further research to improve the quality of learning and the level of student understanding.